In vitro anti-allergic activity of alpha-cyclodextrin moringin complex in rat basophilic leukemia (RBL-2H3) cell line - Alnakeeb, Ebtisam Yousef A (2023)
Allergic disease has become a more prominent public health problem. According to the World Health Organization (WHO), the disease affects 30–40% of the world's population. The most common diseases associated with allergies are asthma, atopic dermatitis, allergic rhinitis, and pollen diseases. In Malaysia, the prevalence rate of allergic rhinitis (AR) was estimated at 7.1%, higher than other Southeast Asian countries. Therefore, the strategies of using phyto-therapeutic agents as alternative sources for antiallergic therapy have become necessary. Moringa oleifera Lam is a tropical plant widely used in traditional medicines and possesses antioxidant, antimicrobial, and antiinflammation properties. Its beneficial effects are believed due to the presence of isothiocyanate (ITC), which is known as moringin (MG). The plant also has been traditionally used to alleviate allergic conditions; however, the bioactive compound in the form of alpha-cyclodextrin moringin (α-CD/MG) complex and its anti-allergic effects remain unexplored. Thus, the purpose of the present study was to investigate the anti-allergic effects of a new formulation of M. oleifera-derived 4-(α-Lrhamnopyranosyloxy) benzyl isothiocyanate as a complex with alpha-cyclodextrin α- CD/MG on rat basophilic leukaemia (RBL-2H3) cell line. NMR showed protons H7, H8, and H9 of moringin (benzyl moiety) with alpha-cyclodextrins proton H3 was involved in the complex formation. The cell proliferation was examined by 3-(4,5- dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H tetrazolium, inner salt (MTS) assay reagent to determine the concentration of α-CD/MG with high cell viability. Chemical shifts of H7, H8, and H9 protons were observed due to interactions between alpha-cyclodextrin and moringin molecules. Low concentrations of α-CD/MG (5, 2.5, 1.25μM) showed no toxicity against RBL-2H3 at 24, 48, and 72 hours, while a higher concentration (10μΜ) showed significant toxicity. For in vitro model of immunoglobulin E (IgE)-mediated mast cell degranulation, monoclonal antidinitrophenyl (DNP) IgE-sensitised RBL-2H3 cells were pre-treated with α-CD/MG before being challenged with dinitrophenyl-bovine serum albumin (DNP-BSA) to induce degranulation. The anti-allergic activity of the complex and ketotifen fumarate as a positive control was evaluated for the early and late phases of allergic reactions. The early phase was determined based on the inhibition of beta-hexosaminidase (β- hexosaminidase) and histamine release; while the late phase was based on the inhibition of interleukin (IL-4), tumour necrosis factor (TNF-α), and prostaglandin D2 (PGD2) release. Interestingly, the results showed that α-CD/MG significantly inhibited mast cell degranulation by inhibiting β-hexosaminidase and histamine release for early phases at concentrations of 5, 2.5 μM and 5, 2.5, 1.25 and, 0.625 μM respectively with p<0.005. Similarly, 5, 2.5, 1.25 and, 0.625 μM of α-CD/MG significantly inhibited TNF-α and PGD2 (P<0.001) during late phases. On the other hand, IL-4 was significantly inhibited at the concentration of 5, 2.5 and 0.625 μM (p< 0.001) compared with the negative control. Therefore, the study suggested that α-CD/MG potentially has an anti-allergic activity by inhibiting both early and late phases of allergic reactions.